2021
DOI: 10.1371/journal.pone.0246305
|View full text |Cite
|
Sign up to set email alerts
|

Peguero-Lo Presti criteria for the diagnosis of left ventricular hypertrophy: A systematic review and meta-analysis

Abstract: Background The Peguero-Lo Presti criteria are novel electrocardiographic (ECG) diagnostic criteria for the detection of left ventricular hypertrophy (LVH) and represent the sum of the amplitude of the deepest S wave in any lead with the S wave in lead V4 (SD+SV4). The diagnostic efficacy of the Peguero-Lo Presti criteria in LVH is still debatable. We aimed to test the sensitivity and specificity of the Peguero-Lo Presti criteria and compared them with those of the Cornell voltage index to assess their overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
(17 reference statements)
1
5
1
4
Order By: Relevance
“…Furthermore, in the literature, the comparison between the ECG and the ECHO is a common methodology for the evaluation of electrocardiographic criteria in the diagnosis of LVH. Since the publication of the Peguero-Lo Presti criterion, several studies have been carried out in this way in order to evaluate its performance, including a meta-analysis, whose results were similar to those found in our work [19][20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, in the literature, the comparison between the ECG and the ECHO is a common methodology for the evaluation of electrocardiographic criteria in the diagnosis of LVH. Since the publication of the Peguero-Lo Presti criterion, several studies have been carried out in this way in order to evaluate its performance, including a meta-analysis, whose results were similar to those found in our work [19][20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 75%
“…Regarding specificity, this criterion obtained a performance of 82.1%. In the meta-analysis by Yu et al, which covered five studies, the sensitivity found for the Peguero-Lo Presti criterion was 52%, while the specificity was 85% [ 20 ]. The results of both studies were similar to the findings for eccentric LVH in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertrophic cardiomyopathy is electrocardiographically characterised by left ventricular hypertrophy measured by SOKOLOW-LYON-index above 3.5 mV [2] or LEWIS-index above 1.6 mV [3], Cornell criteria above 2,0 mV for females and above 2,8 mV for males [4], Peguero-LoPresti ECG criteria above 2.3 mV for females and 2,8 mV for males [5], right ventricular SOKOLOW-LYON-index [6], signs of biventricular hypertrophy criteria [7] and pathologic Q-waves and T-wave inversions [8] Echocardiographically, HCM is characterised by asymmetrical left and right ventricular hypertrophy and usually with abnormalities of mitral valve with leaflet elongation, chordae and papillary muscle abnormalities enhancing left ventricular outflow tract obstruction as demonstrated in the three patients of this family.…”
Section: Discussionmentioning
confidence: 99%
“…7 Alat diagnostik yang luas tersedia, bersifat non invasif, mempunyai biaya yang rendah serta yang umum digunakan untuk mendiagnosis hipertrofi Salsa Oktarin Letmi 61 ventrikel kiri adalah elektrokardiografi (EKG). 7,10,13 Terdapat kriteria dalam mendiagnosis hipertrofi ventrikel kiri melalui pemeriksaan EKG seperti Voltase Sokolow-Lyon dan Voltase Cornell. 14 Sensitivitas EKG dalam mendiagnosis umumnya masih rendah.…”
Section: Pendahuluanunclassified